Sexual citizens : the legal and cultural regulation of sex and belonging - Cossman, Brenda 1960- (Stanford University Press, 2007)
"This book explores the relationship between sex and belonging in law and popular culture. Former sexual outlaws have challenged their exclusion and are being incorporated into citizenship, but as citizenship becomes more sexed, it also becomes more privatized and self-disciplined. Brenda Cossman explores these contesting representations of sex and belonging in film, television, and legal decisions. She examines a broad range of subjects, from gay men and lesbians, pornographers, and hip-hop artists, to women selling vibrators, adulterers, and single mothers on welfare."--BOOK JACKET.